Implementasi Manajemen Lembaga Pendidikan Melalui Pembelajaran Online - Mubarok, Ramdanil (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI SANGATTA Kab. Kutai Timur., 2023)
The aim of this research is to determine the management of educational institutions in online learning, which includes planning, organizing, implementing, and evaluating. Online learning problems and solutions, so that with good management, it is hoped that educational institutions will be better prepared and more effective in implementing online learning. This research is qualitative, with a focus on examining documents related to educational institutions and documents related to online learning, such as research reports, journals, books, magazines, and other literature. As a result, educational institutions manage online learning, starting with planning, organizing, implementing, and evaluating to ensure a good, effective, and efficient teaching and learning process. Problems faced by teachers include weak IT mastery and limited access to student supervision. Students are less active in participating in learning due to limited supporting facilities and internet network access, and parents have limited time to accompany their children when studying online. These various problems can be overcome by increasing competence in mastering IT, intensive supervision involving the role of parents, and giving manual tasks.